The Sufi Path of Dialetheism: Gluon Theory and Wahdat al-Wujud. Issue 2 (3rd April 2018) - Zolghadr, Behnam
Abstract : The theory of Wahdat al-Wujūd, or as it is called in English the Oneness of Being, is the core idea of Sufism. The founder of this theory is Ibn 'Arabī. There are contradictions in Ibn 'Arabī's theory of the Oneness of Being. The most important one, which is my main concern in this essay, occurs in his explanation of the relation between Being, which is, according to him, the only real being, and other beings. According to Ibn 'Arabī, Being is identical and also non-identical with beings. Different philosophers, through hundreds of years, tried to dissolve such contradictions, by proposing consistent readings of Ibn 'Arabī's theory of the Oneness of Being. I will not follow this path. Instead, I take the theory of the Oneness of Being to be a dialetheic one, that is, according to this theory there are true contradictions. Thus, I claim that one can have a paraconsistent semantics of the theory of the Oneness of Being. To do so, I appeal to Graham Priest's Gluon theory. Gluon theory concerns the problem of unity, that is, what makes the plurality of an object's parts into a whole? I give a translation of the theory of the Oneness of Being into Gluon theory, and show how Gluon theory explains the theory of the Oneness of Being.